Awareness and Knowledge of Pneumococcal Vaccination in Cardiology Outpatient Clinics and the Impact of Physicians' Recommendations on Vaccination Rates - Ekin, Tuba; Kis, Mehmet; Gungoren, Fatih; Akhan, Onur; Atici, Adem; Kunak, Aysegul Ulgen; Ergene, Asim Oktay (Mdpi, 2023)
Aim: We aimed to evaluate the awareness of pneumococcal vaccination (PCV13, PPSV23) in general cardiology outpatient clinics and impact of physicians' recommendations on vaccination rates. Methods: This was a multicenter, observational, prospective cohort study. Patients over the age of 18 from 40 hospitals in different regions of Turkey who applied to the cardiology outpatient clinic between September 2022 and August 2021 participated. The vaccination rates were calculated within three months of follow-up from the admitting of the patient to cardiology clinics. Results: The 403 (18.2%) patients with previous pneumococcal vaccination were excluded from the study. The mean age of study population (n = 1808) was 61.9 +/- 12.1 years and 55.4% were male. The 58.7% had coronary artery disease, hypertension (74.1%) was the most common risk factor, and 32.7% of the patients had never been vaccinated although they had information about vaccination before. The main differences between vaccinated and unvaccinated patients were related to education level and ejection fraction. The physicians' recommendations were positively correlated with vaccination intention and behavior in our participants. Multivariate logistic regression analysis showed a significant correlation between vaccination and female sex [OR = 1.55 (95% CI = 1.25-1.92), p < 0.001], higher education level [OR = 1.49 (95% CI = 1.15-1.92), p = 0.002] patients' knowledge [OR = 1.93 (95% CI = 1.56-2.40), p < 0.001], and their physician's recommendation [OR = 5.12 (95% CI = 1.92-13.68), p = 0.001]. Conclusion: To increase adult immunization rates, especially among those with or at risk of cardiovascular disease (CVD), it is essential to understand each of these factors. Even if during COVID-19 pandemic, there is an increased awareness about vaccination, the vaccine acceptance level is not enough, still. Further studies and interventions are needed to improve public vaccination rates.
Keywords: awareness of vaccination; pneumococcal vaccine; prevention of cardiovascular diseases